Knowledge Level of Watershed Farmers about Agro-forestry andSilvi-pasture Practices - A Study in Karnataka (Indian Journal of Extension Education, 2010)
This sutdy was conducted to asses to knowledge level of watershed farmers about agro-forestry and silvi pasture practices in Karnataka. Ten farmers were selected from 18 villages under watershed project through random sampling procedure. Results shown that majority of farmers had sufficent knowledge of all the agro forstry and silivi-pasture models alongwith practices and their economic advantages. Results revealed that farmers had knowledge of most of the species used in different modules of agro-forestry and silvi-pastural system. The association between education, farm size, animals owned, annual income, material possesion, extension participation, environmental awareness, deferred gratification with level of knowledge of the farmers was highly significant. Participation of farmers in the activiation of various social organisations such as panchayat institutions, cooperative, farmers club, etc. had contributed greatly for increasing knowledge of farmers.